Pemodelan Sistem Informasi Penjualan Tiket Pada PT. Karya Nusa Mandiri - Yohannes Yahya Welim (Prosiding SISFOTEK, 2018)
The development of information technology from various fields is very satisfactory therefore every company trying to make or want to have an information system that can meet the needs of the company. The role of Information Systems is currently in addition to the required company and also produces the information needed as a decision by the leadership of the company. PT. Karya Nusa Mandiri which is a company in the field of event management. for recording sales data and sales quotation quote data, this document is managed by one or more people. The problem that occurs is the distribution of ticket sales quota takes a long time, the sales quota is not sold out because the sales quota division is uneven, Sales Data often come late so that in decision making is also often late, and not appropriate, Search Data transactions are scattered and do not have the same standards cause the search process is often not appropriate, Often wrong in recording sales data so that the data process becomes inaccurate, Promoters difficult to get sales data quickly and precisely. With this system can complete Outlet Quota distribution can be done more efficiently, recorded quickly and appropriately so that no more sales quotas that have not been divided and sales quotas can be sold out, on-line ticket sales can serve customers quickly and avoid going double exchange of tickets, Promoters can access sales data quickly without waiting for settlement from Counter Administration, Search process sales data can be done more quickly and more efficiently